Modernisasi dalam Perspektif Samuel P. Huntington - Alamsyah Alamsyah; Syarifuddin Syarifuddin (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This article describes the social and cultural changes in human life that are moving toward modernity. Today's social scientists seem concerned about modernization but tend to use Western industry as a reference for modern models. As Donald Eugene Smith assumed, the world has experienced